SCIATICA AND LUMBAGO IN HOSPITALIZED COVID-19 PATIENTS - Ilić, Jovan; Kostić, Aleksandar; Stojanović, Nikola; Djordjević, Marija; Kostić, Emina; Nikolov, Vesna; Mitić, Radisav (Acta medicae Medianae, 2023)
Clinical symptoms in patients infected with COVID-19 vary from asymptomatic and very mild conditions to severe multi-organ failure, severe pneumonia and septic shock. Although it is relatively common in the non-COVID population, lumbago and sciatica in hospitalized COVID-19 patients have not been sufficiently investigated and reported in the scientific literature. Therefore, the aim of our research was to examine the frequency of sciatica and lumbago, as well as their characteristics in hospitalized COVID-19 patients. The research included 119 patients with confirmed COVID-19 infection with a Real-Time Polymerase Chain Reaction assay for SARS-Cov-2. The presence of sciatica and lumbago were assessed based on the anamnestic data, available medical records of patients and clinical examination. In our study a total number of 39 patients (68.42%) with a previous history of sciatica and lumbago had recurrence of lower back pain. On the other hand, in the group of patients without a previous history of sciatica and lumbago, 30 patients (48.38%) experienced lower back pain for the first time. There was a statistically significant relationship between a previous history of sciatica and lumbago and the recurrence in hospitalized Covid-19 patients (LR = 25.317; p = 0.000). Low back pain and lumbosialgia in hospitalized COVID-19 patients correlate with the length of hospitalization, patient age and vaccination status. There was a high chance that patients with a previous history of lumbago and sciatica may experience a relapse during COVID-19 hospitalization.
Keywords: COVID-19, sciatica, low back pain, COVID-19 vaccines